Model-based analysis of the limits of recycling for its contribution to climate change mitigation; Modellgestützte Analyse der Grenzen des Beitrags von Recycling zum Klimaschutz - Philipp Schäfer; Mario Schmidt (Sustainability Management Forum, 2021)
The concept of Circular Economy (CE) and its main strategy recycling are seen as one of the most important measures to achieve sustainable development. Meanwhile, however, concerns are being raised in the scientific community about the conceptualization and orientation of CE. One major issue is that CE is in danger of becoming an end in itself, with the goal of completely closed material cycles. Its contribution to sustainable development is gradually fading into the background. To contribute to this ongoing discussion, we focus in our article on the recycling of metals as part of CE and its contribution to climate protection, as one of the main aspects of sustainable development. Based on life cycle assessment and substance flow modelling carried out in our previous works, we show that metal recycling in most cases requires much less energy and therefore results in much lower greenhouse gas (GHG) emissions than primary production. However, this is by no means without limitations. We show empirically that metal concentration is a~significant factor that determines the energy required for recycling. If the metals are too diluted in the technosphere, as it is indeed the case for several metal applications, their recycling require much more energy than the alternative primary production, and thus intensifying rather than mitigating climate change.
Keywords: 650; Climate change; Cumulative energy demand; End-of-life recycling rates; Metal concentrations; Metal recycling